Simultaneous Estimation of Thiocolchicoside and Diclofenac Potassium in Tablet Formulation by UV Spectrophotometry - Balasubramaniam, A.; S. Chouhan, Kuldeep; K. Narware, Mithilesh (Asian Journal of Chemistry, 2011)
A simple, specific, accurate, precise and reproducible method has been developed and validated for the simultaneous estimation of thiocolchicoside and diclofenac potassium in pharmaceutical formulation by UV-spectrophotometry, which includes simultaneous equation method (method A) and absorbance ratio method (method B). For the development of method A, wavelengths were selected as 260 nm lmax for thiocholchicoside and 277 nm lmax for diclofenac potassium, while for method B, 277 nm lmax was selected for the diclofenac potassium and 266 nm was the isoabsorptive point of thiocholchicoside and diclofenac potassium. Both drugs follow Beer- Lambert's law at the selected wavelengths in concentration range of 5-25 μg/mL for thiocholchicoside and 5-25 μg/mL for diclofenac potassium. The per cent recoveries of the drugs were found to be nearly 100 % representing the accuracy of both the methods. Validation of the proposed methods was carried out for its accuracy, precision and ruggedness according to ICH guidelines. The proposed methods can be successfully applied in routine work for the determination of thiocholchicoside and diclofenac potassium in a combined dosage form. Also, the method B can be applied for estimation of thiocholchicoside even in presence of the diclofenac potassium in the formulation matrices without interference.